СЎЗЛАШУВ МАДАНИЯТИНИНГ МИЛЛИЙ ХУСУСИЯТЛАРИ - Юсупова, Г.; Бобожонов, М.; Юсупов, А. (SCIENCE and SOCIETY, 2022)
This article talks about the national features of the Uzbek speech culture. In speech communication, the relationship between the speaker and the listener is extremely important, and conversational culture is the art of using each language unit depending on the situation, based on the norms adopted over the years. Speech communication means the joint and cooperative use of verbal and non-verbal means in the process of communication.